Role of IL-10 in inhibiting protective immune responses against infection with heterologous Plasmodium parasites. (June 2019) - Nakamae, Sayuri; Kimura, Daisuke; Miyakoda, Mana; Sukhbaatar, Odsuren; Inoue, Shin-Ichi; Yui, Katsuyuki
Abstract: Malaria is induced by infection with Plasmodium parasites, which are genetically diverse, and the immune response to Plasmodium infection has both allele-specific and cross-reactive components. To determine the role of the cross-reactive immune response in the protection and disease manifestation in heterologous Plasmodium infection, we used infection models of P. chabaudi chabaudi (Pcc) and P. berghei ANKA (PbA). CD4 + T cells primed with Pcc infection exhibited strong cross-reactivity to PbA antigens. We infected C57BL/6 mice with Pcc and subsequently treated them with an anti- Plasmodium drug. The Pcc-primed mice exhibited reduced parasitemia and showed no signs of experimental cerebral malaria after infection with PbA. CD4 + T cells from the Pcc-primed mice produced high levels of IFN-γ and IL-10 in response to PbA early after PbA infection. The blockade of IL-10 signaling with anti-IL-10 receptor antibody increased the proportion of activated CD4 + and γδ T cells and the IFN-γ production by CD4 + T cells in response to PbA antigens, while markedly reducing the levels of parasitemia. In contrast, IL-10 blockade did not have a significant effect on parasitemia levels in unprimed mice after PbA infection. These data suggest a potent regulatory role of IL-10 in the cross-reactive memory response to the infection with heterologous Plasmodium parasites leading to the inhibition of the protective immunity and pathogenesis. Graphical abstract: Unlabelled Image Highlights: CD4 + T cells strongly cross-react to heterologous Plasmodium antigens. Cross-reactive CD4 + T cells produce IL-10 in response to heterologous antigens. IL-10 inhibits protective immune response to heterologous parasite infection.